Analysis of precipitation characteristics in Palembang city - Oemiati, Nurnilam; Arfan, Muhammad; Faulia, Sera (International Journal of Engineering and Technology, 2024)
Geographically, Palembang is located at 2°59′27.99″S 104°45′24.24″E. The area of Palembang city is 400.61 km², with an average height of 8 meters above sea level. The climate of Palembang is a tropical climate with relatively humid winds, with wind speeds ranging from 2.3 km/hour to 4.5 km/hour. Annual precipitation ranges from 2,000 mm to 3,000 mm. This research was conducted in Palembang city. The purpose of this research is to analyze the precipitation characteristics according to the rainfall data in Palembang city. The aim of this research is to determine the analysis of precipitation intensity using the Mononobe method to obtain Intensity-Duration-Frequency (IDF) values. Based on the results of calculating the precipitation intensity using the mononobe method, a value of 38.60465 mm/hour with a duration of 60 minutes over a return period of 10 years can be classified as very heavy rain. From the IDF curve, the character of the rain shows that heavy rains last only for a short duration, this shows that heavy rains last for a short time and conversely heavy rains can last for a long time.